La prison des femmes de Tifelfel : Enfermement et corps en souffrance - Khedidja Adel (L’Année du Maghreb)
In the Aurès mountains, at the end of November 1954, the administration and the army are at war, the military operations intensify: the bombings target the collective granaries and their precious provisions, the evacuation of the villages is generalized ... The French army instrumentalizes women as a tool of terror and humiliation, attacking men and their dignity and shaking up the entire social fabric!This contribution highlights a very singular jail - erected in August 1955 - and intended for the wives of the ‘maquisards’ of the Oued el Abiod valley between the djebels Ahmar Khaddou and Lazreg, at the village of Tifelfel (2000 inhabitants). Today, there is no longer any material trace of this place of detention. The archives are mute as were the women in their self-imposed silence since independence. Arrested, subjected to violent interrogations and then locked up, these women buried the memory of this traumatic period. But these traumas have been lastingly embedded in their bodies, bodies that are the territory of family identity in this war context. Our investigation aims to reconstruct this fragment of history based on the testimonies of former prisoners that are still alive. Interviews that attempt to reconstruct this difficult period, address the exactions, the tortures, the fears and the daily life of their incarceration. But the voices of these women, many of whom are still in mourning, only partially restore the trials and sufferings of these imprisonments. Emotions and injuries are still noticeable and measure the extent of what these women and children have experienced.